STUDI PERANCANGAN KAPAL FERRY RO-RO MODEL KATAMARAN DI PERAIRAN DANAU TOBA - Samuel Samuel; Binart Reynaldo Pardosi (Jurnal Rekayasa Mesin, 2022)
Samosir is an island in North Sumatra which is used as a tourist destination because of the beauty of its lake. Crossing to the island of Samosir requires a ship as sea transportation. Based on data from the Ministry of Transportation, Ajibata Port, the process of crossing vehicles on holidays has been delayed due to a surge in passengers during the high season. The purpose of this research is to design/plan a ship to overcome the accumulation of the number of vehicles in the high season. The method used is the comparison ship method. The number of comparison ships is ten ships of the same type and has met the design criteria as a reference in determining the main size of the new ship. Determination of resistance on this catamaran ferry using the Computational Fluid Dynamics (CFD) method. The way CFD works is using the Navier-Stokes equation to describe the turbulence model with k-ε using multiphase water and air flows. The stability analysis was based on the conditions of the four different compartments following the IMO requirements. The motion analysis was based on the wave height on Lake Toba following the 1987 NORDFORSK rules. The results of the ro-ro ferry design resulted in the main dimensions of the LPP being 49.26 m long, 14.32 m wide, 2.4 m laden, and 4 m high. 9 m, Cb demihull 0.54 and a speed of 11 knots. The resistance value generated using CFD simulation is 68.8 KN. Based on the resistance value, two main engines of 253.3 HP are used.